An Analysis of Deep Neural Network Model in Recognition of Mud Cuttings Image for Practical Applications - Zhao, Zhiming; Gao, Wenyang; Chang, Jiabiao; Chen, Yiming; Zhang, Qiushi; Wang, Bo (Journal of petroleum science and technology, 2022)
Traditional mud logging cuttings identification relies on professionals to carry out visual identification and analysis based on experience. The workload is large and subject to the influence of subjectivity, which is likely to cause errors in information extraction and result analysis. Based on applying deep learning theory in image processing technology, ResNet, DenseNet, and SqeezeNet deep neural network models were built according to the classification of cuttings images. The deep neural network models were used to identify the pictures of cuttings subdivision classification. The evaluation indexes, such as stability, robustness, and recognition effect of different models, were compared and analyzed, and the three models were selected according to the best. The results showed that under the Top-2 standard, the deep neural network model was more accurate in recognizing composite cuttings images. In contrast, the SqeezeNet 1_0 model had the best performance in identifying cuttings after synthesizing different evaluation indicators. The final recognition rate of the optimized SqeezeNet 1_0 model reaches 99.48%. In addition, the obtained SqeezeNet 1_0 network model can effectively identify sandstone, mudstone, and conglomerate cuttings on-site and can be extended to the daily identification of composite cuttings.